First Descent art and artifacts from snowboard culture. - Cook, Sarah; Covalla, George; Walter Phillips Gallery, The Banff Centre, Banff; Bellevue Art Museum, Bellevue (Banff : Walter Phillips Gallery - The Banff Centre for the Arts Banff, 2000)
Bros, Ames ; Cook, Sarah ; Estrada, George ; Francey, Spencer ; Gallup, Mark ; Graves, Trevor ; Hudson, Dan ; Koopman, Caia ; Laybourne, Randy ; Pendygrasse, Dano ; McPhee, Michael ; Morris, Ian
Engels
First Descent : art and artifacts from snowboard culture, Walter Phillips Gallery - The Banff Centre for the Arts Banff, December 3, 1999 - January 23, 2000 / Bellevue Art Museum Bellevue, Bellevue (Washington), February 12, 2000 - April 22, 2000
boek